QASIDAH TRAINING OF ELDERLY GROUPS IN SANGGAR "DURIAN SABATANG" JORONG DURIAN KAMANG MUDIK AGAM REGENCY - Emridawati Emridawati; Darmansyah Darmansyah; Sri Aprillia Nura (RANGKIANG: Jurnal Pengabdian Pada Masyarakat, 2021)
Training of Qasidah Sanggar Seniors Group "Durian Sabatang" Jorong Durian Kamang Mudik Kab. Agam is an activity of community service, which aims to build and develop Islamic life in society based on Islamic values as praised by Allah SWT because it seems that some people abandon the teachings of Islam. This devotion is also based on the lack of knowledge of artists in Qasidah. Methodologically this devotion is qualitative, meaning that the Qasidah activity data obtained on the ground is done through research observations that are useful for knowing, understanding, and studying in depth. So that accurate results are obtained to be given the next training well according to the science, ability and ability of participants. It is then described in writing through words and compiled in a scientific report. Methods used: survey methods, lecture methods, demonstration methods, imitation methods, practice methods, and question and answer methods. The results that have been achieved in the form of reports, and the show uploaded to youtube named emridawati. Specifically, the achievements of this training are, Qasidah players get knowledge and professional playing skills as evidenced through Qasidah performances at Tirtasari Jorong Sonsang attractions, such as: giving birth to a good sound aesthetic, stable tempo, can start and close the show while singing and maintaining cohesiveness in playing together. The show received an audience response to be re-displayed at a later time.